Utilization of Ningxiang pig milk oligosaccharides by Akkermansia muciniphila in vitro fermentation: enhancing neonatal piglet survival - Zhang, Longlin; Wu, Zichen; Kang, Meng; Wang, Jing; Tan, Bie (Frontiers in Microbiology, 2024)
Akkermansia muciniphila (A. muciniphila), an intestinal symbiont residing in the mucosal layer, shows promise as a probiotic. Our previous study found that the abudance of A. muciniphila was significantly higher in Ningxiang suckling piglets compared to other breeds, suggesting that early breast milk may play a crucial role. This study examines A. muciniphila's ability to utilize Ningxiang pig milk oligosaccharides.We discovered that A. muciniphila can thrive on both Ningxiang pig colostrum and purified pig milk oligosaccharides. Genetic analysis has shown that A. muciniphila harbors essential glycan-degrading enzymes, enabling it to effectively break down a broad spectrum of oligosaccharides. Our findings demonstrate that A. muciniphila can degrade pig milk oligosaccharides structures such as 3′-FL, 3′-SL, LNT, and LNnT, producing short-chain fatty acids in the process. The hydrolysis of these host-derived glycan structures enhances A. muciniphila's symbiotic interactions with other beneficial gut bacteria, contributing to a dynamic microbial ecological network. The capability of A. muciniphila to utilize pig milk oligosaccharides allows it to establish itself in the intestines of newborn piglets, effectively colonizing the mucosal layer early in life. This early colonization is key in supporting both mucosal and metabolic health, which is critical for enhancing piglet survival during lactation.